Spiritualisme dalam Ikatan Perkawinan Masyarakat Adat Cireundeu Cimahi Jawa Barat - Ana Mayasari; Diana Sukorina (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to examine the meaning and role of spiritualism in marital bonds within the Cireundeu indigenous community in Cimahi, West Java. For the Cireundeu people, marriage is not merely understood as a social bond between two individuals, but rather as a sacred event imbued with profound spiritual dimensions that connect humans with ancestors, nature, and cosmic harmony. This research employs a qualitative method with an ethnographic approach. Data were collected through in-depth interviews with customary leaders and community members, participant observation during traditional marriage ceremonies, and documentation of ritual practices and cultural symbols. The findings indicate that spiritualism in Cireundeu customary marriage is reflected through a series of symbolic rituals, prayers, offerings, and the use of local food in the form of cassava as a staple food representing community cultural identity. These spiritual dimensions function as a means of legitimizing marital bonds, maintaining cosmic balance, strengthening social solidarity, and transmitting customary values to younger generations. The Cireundeu community believes that a marriage conducted without spiritual rituals is not considered valid according to customary norms, even though it is legally recognized by the state. Spiritual values are interpreted as efforts to preserve the sacredness of marriage, maintain family harmony, and ensure the continuity of indigenous culture. This study concludes that spiritualism in Cireundeu indigenous marriage constitutes the core of cultural identity preservation and social structure sustainability amid the challenges of modernization.